Segment financial reporting: historic aspects, current problems and prospects of development - S.F. Legenchyk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Actuality of research in developing methods of segment financial reporting has been grounded. Features of the development of regulatory process for financial reporting segments have been grounded. Three main stages of the system regulating the development of financial reporting segments in the world (the original accumulation of capital regulation, improve accounting standards to harmonize accounting standards) have been highlight and grounded. The theoretical and methodological problems of segment information formation and organization have been identified and analyzed. These problems have been combined in the two groups (general problem forming segment information; domestic problems forming segment information). The future prospects of the financial segment reporting allowing for the regulation of this sphere in Ukraine have been considered. The necessity of the application of positive accounting theory to improve the quality of accounting segment information have been grounded.